Role of laparoscopy in infertility evaluation - Celis López, Alfredo (2015)
Diagnostic laparoscopy is routinely done in the infertile couple initial evaluation and as diagnostic method of tubal pathology and other intrapelvic causes of infertility. In many centers this procedure is accepted as a final procedure in the infertility work up before the couple is subjected to treatment. However, lately its real value has been questioned and there has been a growing tendency to bypass diagnostic laparoscopy in case of a normal histerosalpingography and treat infertility by intrauterine insemination (IIU) or in vitro fertilization (FIV). Currently it is not clear when we should perform diagnostic laparoscopy in the infertility work up. This review analyzes available evidence to assess the role of diagnostic laparoscopy in the infertile couple work up and its repercussion in infertility treatment, and when laparoscopy intervention should be performed in women undergoing assisted reproductive techniques.